Breast cancer-related lymphedema: Symptoms, diagnosis, risk reduction, and management - Fu, Mei R (Baishideng Publishing Group Inc, 2014)
The global burden of breast cancer continues to increase largely because of the aging and growth of the world population. More than 1.38 million women worldwide were estimated to be diagnosed with breast cancer in 2008, accounting for 23% of all diagnosed cancers in women. Given that the 5-year survival rate for breast cancer is now 90%, experiencing breast cancer is ultimately about quality of life. Women treated for breast cancer are facing a life-time risk of developing lymphedema, a chronic condition that occurs in up to 40% of this population and negatively affects breast cancer survivors’ quality of life. This review offers an insightful understanding of the condition by providing clinically relevant and evidence based knowledge regarding lymphedema symptoms, diagnosis, risk reduction, and management with the intent to inform health care professionals so that they might be better equipped to care for patients.